Głos jako medium. Zacznij od emisji głosu.... = Voice as a medium. Start with the voice emission .... - Kataryńczuk-Mania, Lidia (Zielona Góra: Instytut Pedagogiki. Wydział Pedagogiki, Psychologii i Socjologii. Uniwersytet Zielonogórski)
The article concerns the problems associated with the correct voice emission and its functioning in the teaching profession. The author signals selected values of voice emission and reveals fragments of pilot studies on the subject of voice emission and hygiene in the view of pedagogy students.
Keywords: emisja głosu; higiena głosu; ćwiczenia emisyjne; voice emission; voice hygiene; emission exercises